PENGEMBANGAN MEDIA E-LKPD BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD NEGERI REJOSARI 3 - Andriyani, Nia; Witanto, Yuli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low mathematics achievement of sixth-grade students at SD Negeri Rejosari 3 in the topic of ratios, where only 12.5% of students met the Learning Achievement Mastery Criteria (KKTP). The study aimed to develop an E-LKPD (electronic worksheet) based on the tumpeng ethnomathematics model, analyze the feasibility of the medium, and test its effectiveness in improving student learning outcomes. The research method used was Research and Development (R&D) based on an adapted Borg & Gall model. The research subjects consisted of 22 sixth-grade students. Data collection techniques included questionnaires, interviews, and learning outcome tests. Data analysis was conducted through validity and reliability tests, normality tests, paired-sample t-tests, and N-Gain tests. The results showed that the E-LKPD media was deemed highly feasible, with a media expert validation score of 90% and a content expert validation score of 85%. The medium was also proven effective in improving student learning outcomes with a significance value of 0.00 (p < 0.05) and an N-Gain score in the moderate category. The conclusion of this study is that the ethnomathematics-based E-LKPD on tumpeng is suitable and effective for use as a learning medium to improve elementary school students’ mathematics learning outcomes.